Pretreatment predictors of adjuvant chemoradiation in patients receiving transoral robotic surgery for squamous cell carcinoma of the oropharynx: a case control study. Issue 1 (December 2016) - Subramanian, Harry; Park, Henry; Barbieri, Andrea; Mahajan, Amit; Judson, Benjamin; Mehra, Saral; Yarbrough, Wendell; Burtness, Barbara; Husain, Zain
Abstract Background The purpose of this study was to identify preoperative patient characteristics associated with the incidence of positive surgical margins or lymph node extracapsular extension (ECE), which necessitate adjuvant chemoradiation after transoral robotic surgery (TORS). Methods We conducted a single institution retrospective study of 34 consecutive patients with primary oropharyngeal cancer who underwent TORS. All imaging was reviewed by a single neuroradiologist. Surgical margins and ECE status were determined by a single head and neck pathologist. Associations of preoperative patient characteristics with positive surgical margins and lymph node ECE were examined using univariate analysis. Independent predictors of these outcomes were determined using logistic regression. Results Preoperatively, the majority of patients had early-stage disease (7 cT1 and 21 cT2; 10 cN0). Positive margins occurred in 4 (12 %) patients. A clinically positive lymph node was seen in 23 (68 %) patients. Neck dissection was performed in 29 (85 %) patients, among whom 19 had a pathologically positive lymph node and 15 had nodal ECE. Logistic regression showed that larger preoperative lymph node size was an independent predictor of ECE (odds ratio, 13.32 [95 % CI, 1.46–121.43]). Among the 21 patients with a clinically positive lymph node who underwent neck dissection, ECE was present more often in patients with a preoperative node size ≥ 3.0 vs. < 3.0 cm (92 % vs. 44 %, P = 0.046). There was no patient characteristic associated with positive margins. Conclusions Patients with a larger preoperative lymph node appear more likely to have ECE, and thus be treated with chemoradiation after TORS, with a potentially higher rate of toxicity. Lymph node size should be taken into account when deciding upon treatment approaches. Further research is needed to validate these results.